John Dewey - Moore, Philip B., 1975- author.
1 online resource.
Keywords: "This concise biography tells the story of John Dewey, a pioneer of pragmatism and the first original school of philosophy created in America. The school was born out of a specific historical context, in the wake of a country at war with itself, and in response to the rapid changes of industrialization. Dewey's pragmatism celebrated human intelligence and agency and the promise that tomorrow could be better than today. For Dewey, pragmatism was the philosophy of democracy. Dewey lived from just before the Civil War to just before school integration. As such, the book touches on many key moments in American history, from social reform in turn of the century Chicago, to censorship during world war one, and to the government's responsibilities in the Great Depression. It covers all this in the context of the life of a man whose ideas helped shape American culture and intellectual life. John Dewey: Prophet of an Educated Democracy will appeal to students, scholars, and all those interested in American philosophy and history of the 19th and 20th centuries. It will also compliment humanities courses on American philosophy, history, and intellectual traditions"--